2005
DOI: 10.1111/j.1741-5705.2004.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Scandal, Elites, and Presidential Popularity: Considering the Importance of Cues in Public Support of the President

Abstract: Previous research on presidential job approval has neglected to consider how elites influence public assessments of the executive, particularly as it applies to potentially private misconduct. This article suggests that, in the aftermath of a major political event (such as a scandal), citizens look to elite rhetoric as a barometer of issue importance. Utilizing two distinct experimental designs, I show that, in the wake of a personal scandal, subjects rely upon elite cues to place the events in some political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…By covering some stories but not others, the media increases the salience of certain issues (Iyengar and Kinder ) and primes the public to consider those issues when evaluating leaders and ascribing responsibility (Edwards, Mitchell, and Welch ; Iyengar ; Kelleher and Wolak ; Krosnick and Kinder ). Studies show that presidents themselves can affect their own approval by priming the criteria that citizens use for evaluation (Druckman and Holmes ; Jacobs and Shapiro ), and those citizens look to elite rhetoric as a barometer for issue judgments after major political events (Woessner ). These studies of presidential approval mirror studies that have shown the manipulation of voter perceptions by politicians to influence attributions of responsibility in a similar way (McGraw ; McGraw, Best, and Timpone ).…”
Section: Motivated Reasoning and Partisanship In The Attribution Processmentioning
confidence: 99%
“…By covering some stories but not others, the media increases the salience of certain issues (Iyengar and Kinder ) and primes the public to consider those issues when evaluating leaders and ascribing responsibility (Edwards, Mitchell, and Welch ; Iyengar ; Kelleher and Wolak ; Krosnick and Kinder ). Studies show that presidents themselves can affect their own approval by priming the criteria that citizens use for evaluation (Druckman and Holmes ; Jacobs and Shapiro ), and those citizens look to elite rhetoric as a barometer for issue judgments after major political events (Woessner ). These studies of presidential approval mirror studies that have shown the manipulation of voter perceptions by politicians to influence attributions of responsibility in a similar way (McGraw ; McGraw, Best, and Timpone ).…”
Section: Motivated Reasoning and Partisanship In The Attribution Processmentioning
confidence: 99%
“…Much of the resulting empirical scholarship focuses on the consequences of scandal, whether for its perpetrators, those associated with them, or the larger polity. In addition to negatively affecting a politician's public approval ratings (Simon and Ostrom 1989;Zaller 1998;Andolina andWilcox 2000, Renshon 2002;Woessner 2005;Green, Zelizer, and Kiriby 2018), scandals have been shown to affect legislative voting patterns (Meinke and Anderson 2001), the strength of party identification (Chaffee and Becker 1975;Dunlap and Wisniewski 1978;Robinson 1974); the nation's policy agenda and inter-branch relations (Rottinghaus 2015), media coverage of politics (Sabato, Stencel, and Lichter 2001;Puglisi and Snyder 2011;Entman 2012), public trust in government and its assessments of political institutions (Lipset and Schneider 1983;Miller 1999;Bowler and Karp 2004;Green, Zelizer, and Kirby 2018), voter assessments of individual candidates (Lipset and Schneider 1983;Carlson, Ganiel, and Hyde 2000;Funk 1996;Banerjee et al 2014;Green, Zelizer, and Kirby 2018), and the outcome of subsequent elections (Welch and Hibbing 1997;Klasnja 2017;Peters and Welch 1980;Pereira and Waterbury 2018;Jacobson and Dimock 1994;Hirano and Snyder 2018;Chong et al 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While a politician's defense of the scandal may be counterproductive, support from party elites as well as politicians’ spouses may be beneficial. This support may not guarantee survival, but the absence of such support is detrimental (Woessner, ; Stewart et al., ). Cues from elites in both the incumbent's party and the opposition serve to frame the nature and severity of the scandal; these cues are utilized by citizens in their evaluation of the candidate's behavior.…”
Section: Political Scandalsmentioning
confidence: 99%